Name: Kim

Question:

s=2lw+2wh+2hl solve for h

h=?

Hi Kim,
I like the way you have asked this question. You have the expression

s = 2lw + 2wh + 2hl
and you need to perform a sequence of legitimate algebraic steps to arrive at an expression of the form
h = ?
where ? has no h's in it.
The first step is to put all the terms with an h in them on the left side of the equal sign. You can do this by writin the equation

2lw + 2wh + 2hl = s.
There is one term on the left with no h in it so I want to move it to the right side. You can do this by subtracting the same amount, 2lw, from both sides. That is
2lw + 2wh + 2hl - 2lw = s - 2lw
which then simplifies to
2wh + 2hl = s - 2lw
On the left side now both terms have a factor of h. Thus you can take h out as a common factor to get

h(2w + 2l) = s - 2lw
The final step to leave only h on the left side is to divide both sides by (2w + 2l).
^{h(2w + 2l)}/_{(2w + 2l)} = ^{s}/_{(2w + 2l)}
or
h = ^{s}/_{(2w + 2l)}
Cheers,

Penny